IMPLEMENTASI PEMASARAN EXPERIENTIAL DALAM MEMBANGUN LOYALITAS PELANGGAN SAMARASA COFFEE AND RESTO WONOSOBO - Agus Riyadi agus; Evi Rosalina Widyayanti (Jurnal Riset Manajemen Akuntansi Indonesia, 2026)
This study aims to analyze the implementation of experiential marketing in building customer loyalty at Samarasa Coffee and Resto Wonosobo and to identify its supporting and inhibiting factors. This research employs a qualitative descriptive approach with data collection techniques including observation, in-depth interviews, and documentation. The informants consist of the owner, operational manager, barista, loyal customers, and new customers. Data analysis is conducted using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that experiential marketing has been implemented through five main dimensions: sense, feel, think, act, and relate. The sense dimension is reflected in interior design, coffee aroma, and a comfortable atmosphere. The feel dimension is demonstrated through friendly service and positive emotional experiences. The think dimension is realized through café concepts and coffee education. The act dimension is implemented through interactive activities and customer programs. Meanwhile, the relate dimension is reflected in social interaction and customer community engagement. However, the implementation has not been fully optimal and consistent, as indicated by fluctuating customer visits. Supporting factors include human resource quality, ambiance, and business concept, while inhibiting factors include business competition, limited resources, and changing customer preferences. This study concludes that experiential marketing plays an important role in building customer loyalty but requires consistency and better management.